Effect of tillage and irrigation management on radiation use efficiency of wheat (Triticum aestivum) - MEENA, MADANMOHAN; BANDYOPADHYAY, K K; SARANGI, A; PRADHAN, S; KRISHNAN, P (The Indian Journal of Agricultural Sciences, 2022)
Field experiments were conducted during 2015–16 and 2016–17 on wheat (cv HD2967) in a sandy loam soil at ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of tillage and irrigation management on radiation use efficiency (RUE) of wheat. The treatments comprising of three levels of tillage as main plot factor (Conventional tillage, Deep tillage and No tillage) and three levels of irrigation as subplot factor (I1: 1 irrigation, I3: 3 Irrigations and I5: 5 Irrigations) were evaluated in a split plot design. The results showed that there was no significant difference among tillage treatments with respect to extinction coefficient. However, pooled data of 2 years, extinction coefficient due to I5 was significantly higher than that of I3 and I1 by 8.8 and 23.8%, respectively, and extinction coefficient due to I3 was significantly higher than I1 by 13.8%. There was no significant difference among the tillage treatments with respect to radiation use efficiency (RUE) of wheat, but RUE increased significantly with increasing irrigation level. RUE of wheat under I5 was significantly higher than that of I1 and I3 treatments but there was no significance difference between I1 and I3 with respect to RUE of wheat in both the years.